When does the librarianship became a science in Russia? - A. N. Vaneev (Библиосфера)
The main article objective is a terminological analysis of «librarianship» concept. The development of theoretical concepts of librarianship as a science and as a branch of knowledge is explored. The concept of «library thought» and its correspondence with the concept of «the history of librarianship» is analyzed. The author substantiate the idea that the library thought development did not contradict the history of library science and was its important part, librarianship roots should be traced with the emergence of the first libraries. This point of view on the history of librarianship found understanding in the works by I. V. Lukashov, V. V. Skvortsov, M. I. Slukhovsky, Yu. N. Stolyarov and other library scholars. The article deals with polemic questions: when has librarianship been recognized as a science; can the first use of the concept of «librarianship» be considered as a sign of the emergence of library science. The analysis of applying the concept «library science» showed that before the early XX century it was defined as «a systematic presentation of knowledge about libraries organization and the management». The article analyzes dividing the library science into theoretical and practical parts; examines the fate of the theoretical librarianship in frames of «theoretical» discussions taken place in early 1930s, and attempts of Soviet scientists (V. A. Artisevich, I. A. Mesenyashin, N. Ya. Fridieva) to revive the theoretical library science; considers the views of Yu. V. Grigoriev substantiated the library science as independent one. Analysis of the national library science thought development in 1960s-70s of the XX century showed that its development was characterized by a scientific approach, with heightened attention to general theoretical and methodological problems that contributed to forming the librarianship as a science. The article states that in the modern terminology of the national library science there are two concepts: as a librarianship independent science and as a branch of knowledge. Combination into a single term of at least two different «library sciences» leads both to typological and substantial inconsistencies and errors, which can be seen in a variety of theoretical and practical disciplines including the word «librarianship». The author offers two options concerning use of the term «librarianship». The first one is to call the «librarianship» on the western model «library science», and the term «librarianship» applies to various disciplines (library science as a branch of knowledge). The second one is to retain in national science traditional name «librarianship» as a synonym for «library science» and not to use the word «librarianship» in the titles of different library disciplines to avoid confusion.